70 The digital ambulance: electronic patient clinical records in prehospital emergency care - Alison Porter (Abstracts, 2018)
Electronic Records in Ambulances (ERA) is a two-year study examining the opportunities and challenges of prehospital implementation of electronic patient clinical records (ePCR) in the UK. We describe the current state of implementation.